Perception of effort and the allocation of physical resources: A generalization to upper-limb motor tasks - de la Garanderie, Marie Payen; Courtay, Aymeric; Féral-Basin, Camille; Rainville, Pierre; Gaveau, Jérémie; Pageaux, Benjamin (Frontiers in Psychology, 2023)
Purpose: The perception of effort (PE) is widely used to prescribe and monitor exercise during locomotor and resistance tasks. The present study examines the validity of PE to prescribe and monitor exercise during upper-limb motor tasks under various loads and speed requirements. Methods: Forty participants volunteered in two experiments. In experiment 1, we used four PE intensities to prescribe exercise on a modified version of the box and block test (BBT) and a pointing task. We investigated the possibility of monitoring the exercise intensity by tracking changes in PE rating in response to three different tempos or additional weights. Experiment 2 replicated the possibility of prescribing the exercise with the PE intensity during the BBT and explored the impact of additional weights on performance and PE during the standardized version of the BBT. Muscle activation, heart rate and respiratory frequencies were recorded. Results: In experiment 1, increasing the PE intensity to prescribe exercise induced an increased performance between each intensity. Increasing task difficulty with faster movement tempo and adding weight on the forearm increased the rating of PE. Experiment 2 replicated the possibility to use PE intensity for exercise prescription during the BBT. When completing the BBT with an additional weight on the forearm, participants maintained performance at the cost of a higher PE. In both experiments, changes in PE are associated with changes in muscle activation. Conclusion: Our results suggest that PE is a valid tool to prescribe and monitor exercise during upper-limb motor tasks.